Baltic abstract nouns with -i-s and Slavic with -ьje (IE *-iyo-) - Ostrowski, Norbert (Baltistica, 2025)
Lithuanian abstract nouns of the type plõnis (gen. sg. plõnio) ‘thinness’ (← Lith. plónas ‘thin’) are a continuation of IE neuter adjectives with the suffix *-iyo-. A syntactic analysis of Lithuanian neuter adjectives allows us to assume that the change *-iyo- => -i- is the result of the following phonetic change: plónas ‘thin’ → neutr. *plān-ìja- > (loss of /a/) *plānī- > *plāni- > masc. plõnis ‘thinness’. The presented explanation sheds light on, among other things, the emergence of masculine nouns of the type dagỹs ‘thistle’ / Latv. dadzis < *dagijas (Est. takijas). The development of masculine adjectives with  -ijas => -is / -īs is an analogical, not phonetic, process; its starting point was neuter adjectives. Furthermore, the formation of the Baltic declension in -ē- is based on analogy, in accordance with the model proposed by Kuryłowicz (1966; 1975).
Keywords: Baltic languages; noun abstracts; syntax; neuter adjectives